A DESCRIPTIVE STUDY OF THE TEACHER’S TECHNIQUE ON CONTROLLING THE STUDENTS’ MISBEHAVIOR IN SMPN 1 SUKASADA - G.A.D.P., Rini; P.K., Nitiasih; N.W.S., Mahayanti; L.G.R., Budiarta (Universitas Pendidikan Ganesha, 2019)
Students in this era were already being in touch a lot by technology. This is one of the reasons why students in this era were called as digital native students. The purpose of this research was to know the impact of using digital game to improve the digital native students? English learning. Sample of this research were 25 elementary school students that chosen using lottery and they divided into 5 groups based on the digital local story game that they would play. Pre-test, post-test and interview were conducted to measure the improvement of students? English learning. The result of the pre-test and post-test showed the significance difference in the students? score. The result of the study showed that digital games can improve digital native students? English skill.